ANALISIS TOBINâS Q DAN RETURN ON ASSETS SEBAGAI INDIKATOR KINERJA KEUANGAN (STUDI PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA) - , NADYA EKA PUTRI, Ertambang Nahartyo, M.Sc., Ph.D., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Subprime mortgage crisis that became global crisis in 2008 led many companies in the world experience a variety of performance degradation, including companies in Indonesia. Based on that case, the purpose of this research is to analyze companies that listed in Indonesia Stock Exchange (IDX) after the crisis happened as a form of performance assessment. The source of subprime mortgage crisis came from property and real estate industry, so that this research will be focused on property and real estate companies that listed in IDX from 2010-2012. Indicators used in this performance assessment are Return on Assets (ROA) and Tobinâs Q. The result of this research through ROA indicator show that property and real estate companies listed in IDX after the crisis happened are in good condition, or in other words, companies successfully manage their assets to generate desired profit. Meanwhile, through Tobinâs Q indocator, after the crisis happened, property and real estate companies that listed in IDX still have overvalued stock, that means management of companies successfully manage their profit and have high potential to growth. The result of this research may be useful as an additional information to any party who needs it, as reference to next researches, and may enrich academic researches that relate to financial performance assessment.